Infertile partnersʼ coping strategies are interrelated: implications for targeted psychological counseling = Wechselbeziehungen bei den Bewältigungsstrategien unfruchtbarer Partner : Implikationen für eine zielgerichtete psychologische Beratung - Volmer, Léa; Rösner, Sabine; Toth, Bettina; Strowitzki, Thomas; Wischmann, Tewes (Geburtshilfe und Frauenheilkunde, 2017)
Background: Infertility patients often have high stress levels which, in some cases, represent a risk of developing depression or anxiety. The SCREENIVF questionnaire is a validated tool to evaluate such risks. Some coping strategies have been shown to be correlated with infertile couplesʼ levels of stress. Determining which strategies are correlated with higher levels of risk for depression or anxiety could be useful to offer targeted psychological counseling to reduce the risk of depression or anxiety. Materials and Methods: A total of 296 women and men who attended the Fertility Center at Heidelberg University Hospital completed the SCREENIVF questionnaire and the COMPI coping scales. Data were analyzed first on an individual basis and focused on the couple, using the Actor Partner Interdependence Model. Results: On an individual level, active avoidance coping was positively correlated with a higher risk of depression or anxiety in women, while meaning-based coping was negatively correlated with risk in men. When the results of couples were viewed together, women and men using active avoidance coping exhibited higher risk scores as individuals (actor effect), as did their partners (partner effect). Women who used meaning-based coping had positive actor and partner effects. Women using active-confronting coping had a negative partner effect (higher risk score for men). Conclusions: These findings indicate that some coping strategies may have a protective effect while others may increase the risk of emotional maladjustment in infertile couples. Further analysis of coping strategies could help to identify new counseling approaches for infertile patients.